Respuesta :

Answer:

Step-by-step explanation:

5x - 4y = -13

5x - 2y = -19....multiply by -1

-----------------

5x - 4y = -13

-5x + 2y = 19 (result of multiplying by -1)

------------------add

-2y = 6

y = -6/2

y = -3

5x - 4y = -13

5x - 4(-3) = -13

5x + 12 = -13

5x = -13 - 12

5x = - 25

x = -25/5

x = -5

check..

5x - 2y = -19

5(-5) - 2(-3) = -19

-25 + 6 = -19

-19 = -19 (correct)...it checks out

solution is : x = -5 and y = -3 or (-5,-3)

Answer:

Step-by-step explanation:

5x−4y=−13 .....(1)

​5x−2y=−19.......(2)

Multiply (2) by 2 it will give

10x - 4y = -38 .......(3)

Substracting (1) from (3)

10x - 5x - 4y - (-4y) = -19 - (-13)

5x - 4y + 4y = -19 + 13

5x = - 6

dividing by 5

x = -6/5

x = -1 1/5

And putting x = -6/5 in (1)

5x−4y=−13 .....(1)

5(-6/5) - 4y = -13

-6 - 4y = -13

-4y = -13 + 6

-4y = -7

Dividing each term by -4

y = -7/-4

y = 7/4

y = 1 3/4